Glucose, Cholesterol, Total Protein and Growth Factor Insulin-like Type I in Follicular Fluid of River Buffaloes (Bubalus bubalis) - Gallego, Carlos; Pardo, Margarita [UNESP]; Camargos, Aline [UNESP]; Sousa, Diego [UNESP]; Lenz, Maria; Ramos, Alcides [UNESP]; Jorge, Andre [UNESP]; Ladim, Fernanda [UNESP]; Oba, Eunice [UNESP] (Int Buffalo Information Ctr, 2013)
In order to establish the concentrations of glucose, cholesterol, total protein and growth factor insulin-like type I (IGF-I) in the follicular fluid, 26 Murrah breed river buffaloes, between 45 and 70 days postpartum, empty, multiparous, with average live weight of 675 +/- 56 kg and average body condition of 3.5 points on a scale of 1-5, were used in this study. The fluid was collected from dominant follicles with diameters between 8 and 12 mm by OPU, and was not taken into account the stage of the estrous cycle. Using this technique, the wave of follicular development was synchronized six days prior to collection. Biochemical analysis was performed to glucose and cholesterol through the enzymatic colorimetric method using commercial kit glicose CHOLESTEROL GOD-PAP and CHOD-PAP (Kovalent), respectively. Determination of total protein was carried out by using total protein commercial kit (Kovalent) Biuret method, and the readings were performed using absorption spectrophotometry with visible light. Concentration of IGF-I was measured by Radioimmunoassay (RIA) technique using commercial IRMA Kit IGF-I (INMUNOTECH). Descriptive statistics were developed using the PROC MEANS procedure of SAS (2009). Concentration of glucose (4.0 +/- 0.75 mmol / L-1) and IGF-I (340 +/- 129.83 ng / mL (-1)) were higher than those reported by other authors in river buffaloes and cows, respectively. However, cholesterol levels (0.51 +/- 0.12 mmol / L (-1)) and total protein (58.4 +/- 4.43 g / L (-1)) behaved inferior to other studies in same species. The results indicated that there is relationship among the nutritional aspects, diameter of follicles aspirated and productive period in the concentration of biochemical indicators.
Keywords: biochemical profile; follicular fluid; postpartum